Translocator Protein Ligand Etifoxine Attenuates MPTP-Induced Neurotoxicity - Tian, Qi; Yang, Xiaoxia; Du, Juan; Huang, Huachen; Liu, Wei; Zhao, Peng (Frontiers in Molecular Neuroscience, 2022)
Parkinson’s disease (PD) is a neurodegenerative disease, but the currently available treatments for this disease are symptomatic treatments. There is evidence that translocator protein (18 kDa) (TSPO) expression is upregulated in some neurodegenerative diseases, and TSPO ligands have obvious neuroprotective effects. However, the neuroprotective effects and other potential effects of the TSPO ligand etifoxine in PD remain unclear. Therefore, the present study was designed to explore the impacts of etifoxine on a mouse model of PD induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). We found that etifoxine significantly reduced motor function deficits, decreased the loss of tyrosine hydroxylase-positive neurons in the substantia nigra, and attenuated the decrease in striatal dopamine levels in mice that received MPTP. Etifoxine diminished the production of inflammatory mediators and infiltration of leukocytes in the brain after MPTP exposure. In vitro studies suggested that microglia contribute to etifoxine’s neuroprotective effect. The results showed that etifoxine can alleviate MPTP-induced neurotoxicity and neuroinflammation, providing a new idea for the treatment of PD.